Analysis of the Factors Affecting Delay in Housing Projects in XYZ Group) - Panji Bawono Saputro; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2020)
Success in completing projects on time is one of the essential goals, both for the owner and the contractor. XYZ Group, a holding of several companies in the real estate, has delayed more than 53% of housing projects. The impact of delays is time overrun, cost overrun, deviations in the quality, disputes, negative social consequences, arbitration, and idling resources. This paper studied a list of construction delay causes gathered from the literature. It starts by exploring factors causing project delays from the research and finding 48 causative factors, followed by distributing preliminary questionnaires to expert respondents to obtain 23 causes for housing project delays. The primary survey held on 55 respondents consisting of technical directors, project managers, project engineers, quality control, logistics, and project planners. Relative Importance Index (RII) calculated, and according to the highest values, the top five delay causes of housing projects are determined. Objectives of project delays from the owner and contractor are